EROSI DAN SEDIMENTASI PADA SUB DAS AIR BETUNG KOTA PAGAR ALAM BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) - Yogi Pratama; Lily Endah Diansari (JURNAL ILMIAH BERING'S, 2021)
Watershed Area is a land area that receives rain water to then flow it back through one main river to downstream. Watershed section upstream is often the focus of watershed management planning because in addition to its, as acatchment, there are alsonbiophsical links to downstream areas. This study aims to determine the level of erosion and sedimentation in Air Betung sub-watershed. Erosion and sedimentation analysis used the formula USLE (Universal Soil Loss Equation) which was influenced by faktors such as, rain erosion index (R), soil erodibility index (K), slope length and slop (LS), management factor values safe and assement of land coversation factors (CP). Based on the result of the analysis with using the USLE method and approached with ILWIS 3.3 showed that value erosion was 54,565.73 tons/ha/year. From the results of measurements in the large sediment field hovering that occured in Betung sub-watershed was 1.26 grams in 2L water with debit 5.25m3/sec